Molecular activated recombination in divertor simulation plasma on GAMMA 10/PDX. (August 2017) - Sakamoto, M.; Terakado, A.; Nojiri, K.; Ezumi, N.; Nakashima, Y.; Sawada, K.; Ichimura, K.; Fukumoto, M.; Oki, K.; Shimizu, K.; Ohno, N.; Masuzaki, S.; et al.
Highlights: Molecular activated recombination (MAR) leading to plasma detachment has been observed by additional hydrogen gas injection to the divertor simulation plasma. Dependence of balmer line emissions (Hα and Hβ ) on the neutral pressure indicates that the dissociative attachment process in MAR is more dominant than the ion conversion process. The triatomic molecules would play an important role in MAR for the plasma detachment. Abstract: In the tandem mirror GAMMA 10/PDX, molecular activated recombination (MAR) leading to plasma detachment has been observed by additional hydrogen gas injection to the divertor simulation plasma (i.e. end loss plasma) which is exposed to the V-shaped target in the divertor simulation experimental module (D-module). The temperature near the corner of the V-shaped target decreased from ∼23 eV to ∼2 eV as the neutral pressure in the D-module increased. A clear density rollover was observed at ∼2 Pa. A position of the density maximum moves to upstream of the plasma with increase in the neutral pressure and the density near the corner of the target decreases to detach the plasma from the target. After the occurrence of the density rollover, the Balmer β intensity decreases as with the density but the Balmer α intensity continues to increase, indicating the dissociative attachment process in MAR is more dominant than the ion conversion process although the rate coefficient of the former process is lower than that of the latter one, which is calculated by using a collisional radiative model. This would be caused by the MAR process related to triatomic hydrogen molecules which significantly contributed to the detachment process.